S101 Comparing the patient acceptability, sensitivity and specificity of methacholine and mannitol bronchial challenge tests in asthma diagnosis. (11th November 2022) - Freeman, DM; Murray, CS; Simpson, A; Fowler, S; Bennett, M; Wang, R; Kerry, G; Healy, L; Tudge, R; Willmore, L
Abstract : Introduction: Bronchial hyperresponsiveness (BHR) is a key feature of asthma, and different types of bronchial challenge tests (BCT) are used to assist asthma diagnosis. We aimed to compare the sensitivity and specificity, side-effect profile and patient acceptability of methacholine (MethBCT) and Mannitol (MannBCT) challenge tests. Methods: Participants were recruited from the Rapid Access to Diagnostics of Asthma Study (RADicA). RADicA is a prospective cohort study of 3–69-year-olds with suspected asthma. Participants undertake comprehensive clinical assessment and lung function testing, including spirometry, bronchodilator reversibility (BDR), BCTs, Peak expiratory flow variability (PEFv) and exhaled nitric oxide (FeNO). MethBCT is a core part of the study offered to all participants. MannBCT is an optional visit. Participants who attempted both BCTs were asked to complete an acceptability questionnaire. Reasons for stopping a challenge test early were noted but these participants were not included in further analysis. Participants were asked: 1. To report side effects experienced during testing; 2. To rate the effort of the BCT; 3. To rate acceptability of the length of BCT (both using a five-point scale); 4. Whether they would be happy to repeat the BCT; and 5. To state their preferred challenge. For sensitivity and specificity of BCT analysis asthma was defined as ≥2 positive tests using the tests and cut offs from NICE guideline (NG80): FEV1:FVC ≤70% or LLN, BDR ≥12%, PEFv ≥ 20%, FENO ≥35/40ppm. Results: 50 participants attempted both challenges; early termination occurred in 1 MethBCT and 6 MannBCT, 3 participants did not complete a questionnaire. 40 paired questionnaire responses were analysed (45% male; mean(SD): age 30(15.7) yrs; BMI 25.8(5.5) kg/m 2 ). Results are shown in table 1 . Conclusions: Nearly all patients reported side effects when undertaking BCT, with a trend towards more per challenge for MannBCTs. Sensitivity and specificity was slightly higher in MethBCT than MannBCT. Perhaps methacholine is more useful and better tolerated than mannitol but further assessment in a larger study cohort is needed.